2016
DOI: 10.1038/srep37320
|View full text |Cite
|
Sign up to set email alerts
|

Silver-cotton nanocomposites: Nano-design of microfibrillar structure causes morphological changes and increased tenacity

Abstract: The interactions of nanoparticles with polymer hosts have important implications for directing the macroscopic properties of composite fibers, yet little is known about such interactions with hierarchically ordered natural polymers due to the difficulty of achieving uniform dispersion of nanoparticles within semi-crystalline natural fiber. In this study we have homogeneously dispersed silver nanoparticles throughout an entire volume of cotton fiber. The resulting electrostatic interaction and distinct supramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The range of microbicidal properties of Ag NPs is wider than that of antibiotics, and the appearance of resistant bacteria such as MRSA is rare in Ag NP-based materials [115]. The combination of various materials with Ag NP-based materials has been studied [116,117,118,119]. The production of wound dressings and medical catheters coated with Ag NPs has been investigated.…”
Section: Other Medical Applicationsmentioning
confidence: 99%
“…The range of microbicidal properties of Ag NPs is wider than that of antibiotics, and the appearance of resistant bacteria such as MRSA is rare in Ag NP-based materials [115]. The combination of various materials with Ag NP-based materials has been studied [116,117,118,119]. The production of wound dressings and medical catheters coated with Ag NPs has been investigated.…”
Section: Other Medical Applicationsmentioning
confidence: 99%
“…Earlier studies examining silver nanoparticles created inside cotton bers revealed nanoparticles of about 10 nm, which are of equal size to the microbrillar substructures. 12,13 In the MW fabrications described herein, it is presumed that larger copper particles were observed because the particles were present on the ber surface and on the inner surface of the ber hollow portion in addition to nanoparticles because of the microbrillar structure. Regarding the distribution control of the copper component in the ber cross-section, the elemental prole of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As one example of a functional material inside a cotton ber, a method of creating silver nanoparticles within microbrillar substructures has been reported. 12,13 Nevertheless, no versatile method to install diverse functional materials inside of natural bers has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial genetic material (DNA and / or RNA) is attacked by synthetic peptide-conjugated phosphorodiamidate morpholino oligomer (PPMO) (Genetical approach), or bacteria can be killed by specific viruses, or by restoration of missing components of the flora from fecal microbiota to balance the missing population and by recently developed [5,9]. Nanotechnologal approach where many types of nanoparticles and nanocomposites are used to target bacteria as an alternative to antibiotics [10]. Many traditional organic substances such as Manuka honey, tea tree and clove oil, and curcumin are also in vogue.…”
Section: Approaches Towards Elimination Of Antibioticsmentioning
confidence: 99%